Evaluating the Impact of Naturel Disaster Costs on Macroeconomic Indicators: Evidence from BRICS-T Countries - Ceren Pehlivan (Doğal Afetler ve Çevre Dergisi, 2025)
Natural disasters vary in their impact and shape. Following a calamity, countries may incur social, economic, and political losses. Losses have both short- and long-term consequences that affect a wide range of topics. This study attempted to evaluate the theoretical and empirical influence of costs incurred during natural catastrophes on macroeconomic indices. The study used macro indicators such as growth, unemployment, inflation, expenditure, and payment. Each variable was treated as its own model. The study covered the years 2000 to 2022. The association between natural disaster expenses and macroeconomic variables was investigated using panel analysis. Firstly, descriptive statistics for the variables were used in the analysis. The next step was to do the required causality test using horizontal section and delta tests. In accordance with the findings, the Kónya causality test was used. This test reveals a one-way relationship between the natural disaster variable and the growth variable, a one-way relationship from the natural disaster variable to the unemployment variable, a bidirectional relationship between the natural disaster and investment expenditure variables, a one-way relationship between the natural disaster variable and the expenditure variable, and a unidirectional relationship between the natural disaster variable and the It was established that a directional connection existed.